INCIDENCIA DE LA DESIGUALDAD DE LA FORMACIÓN DEL CAPITAL HUMANO EN LA DESIGUALDAD DEL INGRESO REGIONAL EN EL ECUADOR DURANTE EL PERIODO 2007-2016 - Ayala Vivanco, Nayrovi Carolina (2018)
In the present research work, it was proposed to determine the incidence of inequality in the formation of human capital in the inequality of regional income in Ecuador during the period 2007-2016, by means of a regression analysis with panel data and spatial methods. Inequality was calculated by the Gini index, using data from the National Survey of Employment, Unemployment and Underemployment for 214 cantons. To make spatial panel estimations, instrumental variables of the Living Conditions Survey were incorporated in order to correct the endogeneity of the proposed model. The main results showed that before a 1% increase in the inequality of human capital formation, income inequality increases in a range of 0.23% and 0.49%. To capture other human capital endowments, a set of control variables were included, which indicated to be relevant in certain models and income levels. Finally, by spatial techniques, the spatial dependence of the model was confirmed. An implication of economic policy derived from the results establishes the improvement of the quality of public education in the country.